The Effect of Clay Tile Particle Addition on the Flame Retardancy and Impact Toughness of Ramie Fiber-Reinforced Polypropylene Composites - Gibrail, Muhammad; Hastuti, Sri; Listyanda, R. Faiz; Saputra, Eko; Nugroho, Wahyu; Putri, Farika Tono; Indrawati, Ragil Tri; Salahudin, Xander (Mechanical Engineering Department - Semarang State Polytechnic, 2026)
Environmental concerns regarding polypropylene (PP) plastic waste have driven the demand for more sustainable alternative materials through composite development. This study aims to analyze the effect of adding Sokka roof tile particles as a filler on the flame retardancy and impact toughness of ramie fiber-reinforced composites. The composite materials utilize a polypropylene matrix, ramie fiber reinforcement, and Sokka roof tile particles as filler with concentration variations of 2%, 4%, and 6%. The results demonstrate that increasing the filler volume significantly improves the material's flame-retardant properties, with the 6% variation achieving the best thermal performance and the lowest burn rate of 214.27 mm/min. However, in terms of mechanical properties, a decline in impact toughness was observed as the filler content increased; the average energy absorption dropped from 1.075 Joules at 2% concentration to 0.735 Joules at 6%, which is consistent with the decrease in impact strength from 0.0364 J/mm² to 0.0204 J/mm². This phenomenon indicates that while inorganic particles effectively serve as a thermal barrier, excessively high concentrations increase material brittleness, thereby reducing the impact energy absorption capacity. In conclusion, a 6% concentration of Sokka roof tile particles is recommended for applications prioritizing fire safety, while considering the compromise in mechanical strength.